Evaluation of effectiveness of kinesiotaping in supporting of rehabilitation of patients after meniscus injury. Preliminary report - Boguszewski, Dariusz; Tomaszewska, Iwona; Adamczyk, Jakub Grzegorz; Białoszewski, Dariusz (Asian Journal of Medical Sciences, 2014)
Objective: Kinesiotaping (KT) is a method being increasingly more often applied in rehabilitation of movement system. The aim of the study was to assess the effect of kinesiotaping on the rehabilitation result in patients with damaged meniscus. Material and methods: The study enrolled 23 patients (14 women and 9 men) aged between 20 to 41 years. The patients were at random divided into two groups: Group 1 (the experimental group) which received kinesiotaping application, and Group 2 (the control group), which had similar rehabilitation protocol except for the KT application. Results: All participants demonstrated a significant improvement in the range of knee flexion and extension of the injured limb as soon as the end of the first week of the rehabilitation (p<0.001). This tendency persisted in the following weeks until 28th day. Significant swelling reduction was found at patients from the experimental group in all consecutive measurements. The greatest difference (p<0.001) was noted at the beginning of the rehabilitation. After 28 days of rehabilitation, pain intensity and frequency had significantly decreased at all patients (p<0.001). Patients from the control group used analgesics significantly more often. Conclusions: The used KT application contributed to a faster improvement of the range of joint motion and reduction of oedema. A similar reduction in pain intensity was observed at all research participants. However, pain considerably less often forced patients from the experimental group to use analgesics. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11809 Asian Journal of Medical Sciences Vol.6(4) 2015 61-66